COMPARATIVE DISSOLUTION STUDIES OF WARFARIN SODIUM TABLETS: INFLUENCE OF AGITATION RATE, DISSOLUTION MEDIUM, AND USP APPARATUS - LOPEZ, JOSE RAUL MEDINA; ROMAN, LUIS DANIEL MAZON; JIMENEZ, JUAN MANUEL CONTRERAS; RUIZ-SEGURA, JUAN CARLOS (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of this study was to carry out comparative dissolution studies with warfarin sodium reference tablets under the hydrodynamic environments generated by the USP basket and paddle apparatus and flow-through cell using different agitation rates and dissolution media. Methods: Dissolution profiles were obtained with the USP basket and paddle apparatus at 50, 75, and 100 rpm and 900 ml of water as dissolution medium. After this, dissolution profiles of warfarin sodium were obtained with the USP paddle apparatus and flow-through cell method using 0.1 N hydrochloric acid, acetate buffer pH 4.5, phosphate buffer pH 6.8, and water. Spectrophotometric determination at 308 nm was carried out during 30 min. Dissolution profiles were compared with model-independent and model-dependent approaches. Results: Significant differences were found with mean dissolution time and dissolution efficiency at 50 and 75 rpm (*P<0.05). Makoid-Banakar was the best-fit model used to describe the in vitro release performance of warfarin sodium with 50-100 rpm and the USP basket and paddle apparatuses. Significant differences in all calculated parameters were found (*P<0.05) excepting percent dissolved at 30 min with 0.1 N hydrochloric acid and phosphate buffer pH 6.8. Conclusion: More research is necessary to identify the in vitro release performance of poorly soluble drugs under available USP apparatuses considering factors as agitation rate and kind of dissolution media. The knowledge of the in vitro release performance of reference drug products is important for the design of better generic formulations